Survivin Modulators: An Updated Patent Review (2011 - 2015) - Roy, Kislay; Singh, Neha; K. Kanwar, Rupinder; R. Kanwar, Jagat (Recent Patents on Anti-Cancer Drug Discovery, 2016)
Background: Survivin is widely overexpressed in many forms of cancer and studies have related high survivin expression with poor survival rates. Although, there have been several attempts to target survivin, most therapeutics haven’t shown substantial success in clinical trials therefore, authors wish to attract the focus towards many recent therapeutic innovations to target survivin. Objective: Survivin plays an essential role in the cell cycle progression, apoptosis, cell stress response, drug resistance and angiogenesis therefore the prognostic and targeting benefits of survivin have been underestimated. An update on the current and existing therapeutic strategies implemented to target survivin is provided. Therefore, the reader will gain an insight into the recent patents targeting survivin. The review has emphasised on patents for quantification of survivin, survivin peptides as immunotherapeutics, application of survivin promoters, RNA interference of survivin, small molecules inhibitors of survivin and nanoparticles targeting survivin. The review also encompasses the survivin targeted therapeutics being implemented at clinical stages which include survivin targeted immunotherapeutics, peptide-based vaccines, antisense oligonucleotides and chemical inhibitors. Conclusion: We reviewed recent patents based on preclinical anti-survivin therapies reported to date and it was concluded that gataparsen has been most widely used for anti-survivin therapy in clinical trials. It was also concluded that most therapeutic patents were focussed on development of natural anti-survivin therapeutics such as anti-survivin peptides or survivin anti-sense oligonucleotides in the recent years therefore, proving that natural proteins and nucleic acids has an upper hand over chemicals and synthetic drugs.
Keywords: survivin